Fatal penetrating injuries of the chest - Scholtz, Hendrik Johannes (Division of Forensic Medicine and Toxicology, 2018)
In the Republic of South Africa, an autopsy is required in all cases of unnatural death, or in cases where the cause of death is unknown in terms of the Inquest Act of 1959. These are performed at the Salt River Medicolegal Laboratory by Forensic Pathologists and Registrars of the Department of Forensic Medicine and Toxicology of the University of Cape Town. The Salt River Medicolegal Laboratory serves the greater Cape Town area with a population of approximately 2,5 million, including the magisterial districts of Cape Town, Wynberg, Mitchell's Plain and Simonstown. Cape Town has one of the world's highest homicide rates and in 1986 the incidence was 56, 91 100000 population per annum. In contrast, Singapore has a homicide rate of only 2, 5/100 000, while the United States has an overall homicide rate of 7,7/ 100 000 population. In order to document the true impact of penetrating chest injuries, and to place mortality data in perspective, a retrospective descriptive study of all cases with fatal penetrating chest injuries admitted to the Salt River Medicolegal Laboratory in Cape Town during 1990 was undertaken. In 1990, a total of 5 758 cases was admitted to the Salt River Medicolegal Laboratory of which 1834 cases (39%) were the result of homicide. Of the homicide cases, 408 (22%) were the result of firearm injuries. A total of 2044 (35, 5%) cases admitted was deemed to have died of natural causes. This study identified a total of 841 cases of fatal penetrating injuries of the chest admitted during 1990, which constituted 22,6% of all non-natural cases admitted.